The Appraisal and Countermeasure Analysis of the International Competitiveness of Tourism Service Trade in Henan Province (Global Journal of Management and Business Research, 2021)
With the continuous development of the macro-economy and the Internet of transportation and trade worldwide, the status of trade in tourism services is getting higher and higher. Henan has a long history and rich and colorful culture. As the birthplace of Central Plains Civilization, Henan has rich tourism resources. This paper analyzes the export status of the tourism service trade in Henan Province by using relevant data and analyzes the factors influencing the competitiveness of the tourism service trade in Henan Province by using the diamond model; this paper puts forward some suggestions to improve the export competitiveness of tourism service trade in Henan Province.
Keywords: tourism service trade; diamond model; henan province